ANALISIS PENGARUH KUALITAS PELAYANAN KUALITAS, KUALITAS PRODUK, HARGA PRODUK TERHADAP KEPUASAN PELANGGAN DI PENJAHIT REZKY TEXTILE & TAILOR SURAKARTA - Ika Choirun Nisa (JURNAL WIRANOMIKA, 2025)
This study aims to determine the effect of Service Quality (X_1), Product Quality (X_2), and Product Price (X_3) on Customer Satisfaction (Y) at Penjahit Rezky Textile & Tailor. This study uses multiple linear regression analysis analyzed using SPSS 26. The results of the multiple linear regression analysis equation obtained are Y = 2.252 + 0.474X_1 + 0.362X_2 + 0.012X_3 + e. The data used are primary data using the number of respondents 100 sewing service customers at Rezky Textile & Tailor Surakarta. The results of the study indicate that Service Quality (X_1) t count 4.332> t table 1.985 then the hypothesis is rejected, meaning there is a significant influence between the variable Service Quality (X_1) on Customer Satisfaction (Y) at Penjahit Rezky Textile & Tailor Surakarta. Product Quality (X_2) t count 3.996 > t table 1.985 then the hypothesis is rejected, meaning there is a significant influence between the variable Product Quality (X_2) on Customer Satisfaction (Y) at Penjahit Rezky Textile & Tailor Surakarta. Product Price (X_3) t count 0.114 < t table 1.985 then the hypothesis is accepted, meaning there is no significant influence between the variable Price (X_3) on Customer Satisfaction (Y) at Penjahit Rezky Textile & Tailor Surakarta. The results of the F test obtained F count = 22.963 > F table = 2.70 then the Hypothesis is rejected, meaning that together there is a significant influence between the variables Service Quality (X_1), Product Quality (X_2), Price (X_3) on Customer Satisfaction (Y) Rezky Textile & Tailor Surakarta. it can be concluded that 40% of Customer Satisfaction at Rezky Textile & Tailor Surakarta is influenced by Service Quality (X_1), Product Quality (X_2), Price (X_3). While 60% comes from other variables that affect other research models that are not included in this study. Keywords: Service Quality, Product Quality, Price, Customer Satisfaction.